The Role and Effectiveness of Mediators in Resolving Divorce Disputes at the Sekayu Class 1B Religious Court - Putra, M. Ferdi Raihan; Murjaya, Murjaya; Nurcahyani, Ririn Selia (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The issues addressed in this study are: What is the role of the mediator in resolving divorce disputes at the Sekayu Religious Court? What are the supporting and inhibiting factors for mediators during the mediation process? How effective is mediation in resolving divorce disputes at the Sekayu Religious Court? This study uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The obtained data is analyzed in-depth to describe the real role of the mediator as well as the dynamics occurring during the mediation process. The results show that the mediator plays an important role as a neutral party that bridges communication between the disputing husband and wife. The success of mediation is influenced by the mediator's communication skills, the emotional readiness of the parties, and regulatory support from the judicial institution. However, obstacles such as the unwillingness of the parties to reconcile and time constraints during the mediation process often pose challenges. Therefore, mediation at the Sekayu Religious Court is quite effective in some cases, but its effectiveness heavily depends on the conditions of the parties involved and the mediator's skills.